Problems of diagnosis and treatment of chronic ischaemic heart disease combined with chronic obstructive pulmonary disease according to retrospective analysis - Potabashnii , V.A.; Kniazieva , O.V.; Markova , O.Ya. (Medicni Perspektivi, 2021)
Ischaemic Heart Disease (IHD) and Chronic Obstructive Pulmonary Disease (COPD) are common diseases that rank highest in the Global Burden of Disease Study (2019). IHD and COPD are often combined, making diagnosis and treatment of patients difficult in actual clinical practice. The aim of the study was to identify problems in the diagnosis and treatment of patients with a combination of chronic IHD and COPD, based on a retrospective analysis of medical records. Patient’s adherence to treatment was also assessed with the Morisky Scale (MMAS-8). The analysis of 108 inpatient charts with a combination of chronic IHD and COPD was carried out. The quality of diagnosis and treatment of IHD was evaluated in accordance with the order of the Ministry of Health of Ukraine N152 dated March 02 2016, considering the recommendations of the European Society of Cardiology (2019). It was found that smoking history was in 23.1% of patients, a body mass index (BMI) was calculated in 51,9%, and a carotid ultrasound examination was carried out in 7.4% of cases. The total cholesterol level was determined in 59.2% of patients, while the level of low-density lipoprotein cholesterol (LDL-C) was determined in only 43.5%. Transthoracic echocardiography (TTE) was performed in 62.9 % of patients, but stress-echocardiography and exercise ECG were not performed. Daily ECG monitoring was performed in 60.2% of cases. The levels of brain natriuretic peptide (BNP) or N-terminal proBNP (NT-proBNP) were not detrmined to precise etiology of dyspnea. It was also found that beta-blockers (29.6% of patients), ivabradine (11.1% of patients) and statins (65.7% of patients) are seldom administered to patients with IHD and COPD. The targeted doses of these drugs are not reached. Fixed combinations of long-term bronchodilalarors were insufficiently used in therapy of COPD. However, patients' adherence to basic IHD and COPD therapy is weak. 45.4 % of patients were non-adherent to treatment, 43.5% were medium-adherent, and only 11.1% of patients were adherent to treatment.